2022
DOI: 10.1097/mat.0000000000001699
|View full text |Cite
|
Sign up to set email alerts
|

Arterial Carbon Dioxide and Acute Brain Injury in Venoarterial Extracorporeal Membrane Oxygenation

Abstract: Acute brain injury (ABI) occurs frequently in patients receiving venoarterial extracorporeal membrane oxygenation (VA-ECMO). We examined the association between peri-cannulation arterial carbon dioxide tension (PaCO 2 ) and ABI with granular blood gas data. We retrospectively analyzed adult patients who underwent VA-ECMO at a tertiary care center with standardized neuromonitoring. Preand post-cannulation PaCO 2 were defined as the mean of all PaCO 2 values in the 12 hours before and after cannulation, respecti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
2

Relationship

3
6

Authors

Journals

citations
Cited by 19 publications
(9 citation statements)
references
References 30 publications
0
9
0
Order By: Relevance
“…Prior studies with VA-ECMO patients are equivocal. With the benefit of protocolized neuromonitoring and frequent ABG collections, we have previously reported that large delta PaCO 2 in VA-ECMO patients was significantly associated with ICH (OR=2.69; 95% CI=1.18-6.13) but not with composite ABI or mortality(26). Diehl et al found a PaCO 2 drop >20 mmHg was associated with mortality but not ABI in VA-ECMO(24).…”
Section: Discussionmentioning
confidence: 99%
“…Prior studies with VA-ECMO patients are equivocal. With the benefit of protocolized neuromonitoring and frequent ABG collections, we have previously reported that large delta PaCO 2 in VA-ECMO patients was significantly associated with ICH (OR=2.69; 95% CI=1.18-6.13) but not with composite ABI or mortality(26). Diehl et al found a PaCO 2 drop >20 mmHg was associated with mortality but not ABI in VA-ECMO(24).…”
Section: Discussionmentioning
confidence: 99%
“…However, moderate-high hypercarbia may be associated with high intracranial pressure (vasodilation), potentially catastrophic in patients who have already sustained an ABI. In fact, one study in a general venoarterial ECMO population (non-ECPR) found that a large pericannulation drop in Pa co 2 (∆Pa co 2 ) was associated with intracranial hemorrhage (ICH) (31). Studies based on the ELSO registry showed that a large ∆Pa co 2 within 24 hours of cannulation was associated with more ABIs in venoarterial ECMO (32) and poorer survival in ECPR (23).…”
Section: Post-ca Care In Ecprmentioning
confidence: 99%
“…Furthermore, a previous study found that, although the hemorrhagic group had the highest average blood pressure, it had the lowest cerebral tissue oxygenation saturation, suggesting that elevated vascular resistance may lead to poor cerebral perfusion [ 24 ]. The risk factors related to ICH include use of anticoagulants and antiplatelet therapy [ 22 ], female sex [ 25 ], higher pre-cannulation PaCO2 [ 26 ], thrombocytopenia, high transfusion requirements [ 18 ], a large dual-lumen venovenous cannula [ 20 ], ECMO duration [ 17 ], bloodstream infections [ 22 ], renal failure, and dialysis [ 27 ]. Finally, ICH patients are known to have high mortality and morbidity [ 18 ].…”
Section: Patterns Of Ecmo-related Abimentioning
confidence: 99%
“…Seizures are abnormal, paroxysmal electroencephalography (EEG) events that vary from background activity [ 39 ]. Due to the use of sedative drugs and a lack of EEG monitoring, seizure incidence may also be underestimated at 2–6% in patients undergoing VA ECMO [ 5 , 26 ] and 1.3% in VV ECMO adult patients [ 40 ]. Previous studies have claimed that younger pediatric patients have higher occurrence of seizures than older patients [ 41 , 42 ].…”
Section: Patterns Of Ecmo-related Abimentioning
confidence: 99%